Fe and Sn Single-Site-Based Electrodes for High-Current CO2 Reduction in Acid Media and Stable Zn–CO2 Batteries - Hu, Jiajun; Goberna-Ferrón, Sara; Simonelli, Laura; Lopez Salas, Nieves; García, Hermenegildo; Albero, Josep (ACS Applied Energy Materials)

Sustainable Development of Graphene Electrodes for Supercapacitors through Laser Scribing of Agrowaste Derived Lignin - Katwesigye, Samuel; El-Khouly, Mohamed E.; Lopez Salas, Nieves; Khalil, Ahmed S.G. (Materials Science Forum)
The growing rise in agricultural activities has resulted in an increase in unutilized waste which is a significant contributor to greenhouse gas emissions. This has led to a need for sustainable methods to add value to such waste. This work focused on the transformation of agricultural waste into usable products through alkaline treatment to obtain lignin and cellulose, and the evaluation of the derived lignin as a viable carbon precursor in energy storage applications. Laser scribing was used as a fast and simple strategy in producing laser-induced graphene (LIG) electrodes. Lignin was isolated from wheat straw using sodium hydroxide treatment. The pulp from the treatment was subjected to bleaching with sodium chlorite followed by acid hydrolysis to extract microcrystalline cellulose. Fourier-transform infrared spectroscopy (FTIR), Transmission electron microscopy, and Xray diffraction were used for characterization of the materials produced. The fabricated supercapacitor could achieve an areal capacitance (C A ) of 5.12 mF/cm 2 (0.02 mA/cm 2 ). This study illustrated the successful valorization of wheat straw residue into microcrystalline cellulose and the use of extracted lignin in producing graphitic carbon electrodes for supercapacitors.

Optical modulator and electronic apparatus including the same - Güsken, Nicholas Alexander

Unified boson sampling - Bianchi, Luca; Marconi, Carlo; Ares, Laura; Bacco, Davide; Sperling, Jan (Physical Review Research)
Boson sampling is a key candidate for demonstrating quantum advantage and has already yielded significant advances in quantum simulation, machine learning, and graph theory. In this work, a unification and extension of distinct forms of boson sampling is developed. The devised protocol merges discrete-variable scattershot boson sampling with continuous-variable Gaussian boson sampling. Therefore, it is rendered possible to harness the complexity of more interesting states, such as squeezed photons, in advanced sampling protocols. A generating function formalism is developed for the joint description of multiphoton and multimode light undergoing Gaussian transformations. The resulting analytical tools enable one to explore interfaces of different photonic quantum-information-processing platforms. A numerical simulation of unified sampling is carried out, benchmarking its performance, complexity, and scalability. Entanglement is characterized to exemplify the generation of quantum correlations from the nonlinear interactions of a unified sampler.

Locally homogeneous Axiom A flows I: projective Anosov subgroups and exponential mixing - Delarue, Benjamin; Monclair, Daniel; Sanders, Andrew (Geometric and Functional Analysis (GAFA))
By constructing a non-empty domain of discontinuity in a suitable homogeneous space, we prove that every torsion-free projective Anosov subgroup is the monodromy group of a locally homogeneous contact Axiom A dynamical system with a unique basic hyperbolic set on which the flow is conjugate to the refraction flow of Sambarino. Under the assumption of irreducibility, we utilize the work of Stoyanov to establish spectral estimates for the associated complex Ruelle transfer operators, and by way of corollary: exponential mixing, exponentially decaying error term in the prime orbit theorem, and a spectral gap for the Ruelle zeta function. With no irreducibility assumption, results of Dyatlov-Guillarmou imply the global meromorphic continuation of zeta functions with smooth weights, as well as the existence of a discrete spectrum of Ruelle-Pollicott resonances and (co)-resonant states. We apply our results to space-like geodesic flows for the convex cocompact pseudo-Riemannian manifolds of Danciger-Gu\'eritaud-Kassel, and the Benoist-Hilbert geodesic flow for strictly convex real projective manifolds.

Singular cohomology of symplectic quotients by circle actions and Kirwan surjectivity - Delarue, Benjamin; Ramacher, Pablo; Schmitt, Maximilian (Transformation Groups)
Let $M$ be a symplectic manifold carrying a Hamiltonian $S^1$-action with momentum map $J:M → \mathbb{R}$ and consider the corresponding symplectic quotient $\mathcal{M}_0:=J^{-1}(0)/S^1$. We extend Sjamaar's complex of differential forms on $\mathcal{M}_0$, whose cohomology is isomorphic to the singular cohomology $H(\mathcal{M}_0;\mathbb{R})$ of $\mathcal{M}_0$ with real coefficients, to a complex of differential forms on $\mathcal{M}_0$ associated with a partial desingularization $\widetilde{\mathcal{M}}_0$, which we call resolution differential forms. The cohomology of that complex turns out to be isomorphic to the de Rham cohomology $H(\widetilde{ \mathcal{M}}_0)$ of $\widetilde{\mathcal{M}}_0$. Based on this, we derive a long exact sequence involving both $H(\mathcal{M}_0;\mathbb{R})$ and $H(\widetilde{ \mathcal{M}}_0)$ and give conditions for its splitting. We then define a Kirwan map $\mathcal{K}:H_{S^1}(M) → H(\widetilde{\mathcal{M}}_0)$ from the equivariant cohomology $H_{S^1}(M)$ of $M$ to $H(\widetilde{\mathcal{M}}_0)$ and show that its image contains the image of $H(\mathcal{M}_0;\mathbb{R})$ in $H(\widetilde{\mathcal{M}}_0)$ under the natural inclusion. Combining both results in the case that all fixed point components of $M$ have vanishing odd cohomology we obtain a surjection $\check κ:H^ev_{S^1}(M) → H^ev(\mathcal{M}_0;\mathbb{R})$ in even degrees, while already simple examples show that a similar surjection in odd degrees does not exist in general. As an interesting class of examples we study abelian polygon spaces.

Systematic AI Potential Analysis for Sustainable Rough Factory Planning - Kürpick, Dominik; Disselkamp, Jan-Philipp; Lick, Jonas; Hovemann, Aschot; Dumitrescu, Roman (Lecture Notes in Mechanical Engineering)
Abstract Current megatrends are influencing industrial production and leading to ever shorter innovation cycles. The resulting fast pace of production requirements requires an accelerated development of production systems and an associated increase in efficiency in factory planning. Due to its knowledge-intensive activities, rough factory planning promises great potential to be supported in its activities by innovative technologies such as artificial intelligence. However, industrial companies face the challenge to recognize the potential of artificial intelligence (AI) in rough planning and to evaluate possible applications in their business context. As a result, a systematic approach for analyzing AI potential in rough factory planning was developed as part of this work. The system includes a procedural model and several artefacts used in it, which support the identification and evaluation of AI potential in organizations. This approach not only streamlines the planning process but also aligns with sustainable manufacturing principles by enhancing resource efficiency, promoting intelligent system design, and fostering innovation in product development and manufacturing processes.

AI-augmented systems engineering: conceptual application of retrieval-augmented generation for model-based systems engineering graph - Hanke, Fabian; Bita, Isaac Mpidi; von Heißen, Oliver; Weller, Julian; Hovemann, Aschot; Dumitrescu, Roman (Proceedings of the Design Society)
ABSTRACT: This paper presents the MBSE-Graph-RAG framework to address key challenges in Model-Based Systems Engineering (MBSE). Traditional MBSE tools suffer from usability barriers, limited accessibility, and integration challenges. By combining knowledge graphs with Retrieval-Augmented Generation (RAG), the proposed framework enables AI-Augmented engineering through natural language interactions and automated system architecture generation. A systematic literature review establishes a solid research foundation, identifying gaps in AI-assisted MBSE. Key contributions include a structured MBSE-Graph interface, improved usability via Large Language Models (LLMs), and automated graph construction aligned with SysML. A proof-of-concept demonstrates the potential of this approach to enhance MBSE by reducing complexity, improving data accessibility, and supporting engineering collaboration.

Akzeptanz von KI-Lösungen: Analyse der Einflussfaktoren und ihre Relevanz für Mitarbeitende - Dondorf, Verena; Kokilanathan, Kitrujan; Graunke, Jannis; Hobscheidt, Daniela; Dumitrescu, Roman (Vorausschau und Technologieplanung)

Nachhaltigkeit als strategischer Erfolgsfaktor–ein Framework für die unternehmerische Nachhaltigkeitstransformation - Dohmann, Friederike; Hobscheidt, Daniela; Vy Vo, Gia; Kürpick, Christian; Dumitrescu, Roman (Vorausschau und Technologieplanung)

Können LLMs Model-based Systems Engineering ewertung der M SE-Fähigkeiten von LLMs - Bernijazov, Ruslan; Rasor, Rik; Dumitrescu, Roman (Tag des Systems Engineering 2025: Tagungsband Salzburg, 29.-31. Oktober 2025)

A serious game to introduce Systems Engineering in interdisciplinary teams - Könemann, Ulf; Niemeyer, Marcel; Schierbaum, Anja; Dumitrescu, Roman (Procedia CIRP)

Toward a GenAI-Supported Systems Engineering Competency Assessment - Könemann, Ulf; Roby, Derik; Schierbaum, Anja; Dumitrescu, Roman (Tag des Systems Engineering 2025: Tagungsband Salzburg, 29.-31. Oktober 2025)

Auf dem Weg zu einem fähigkeitsbasierten Digital Engineering Zielbild - Wyrwich, Fabian; Hovemann, Aschot; Dumitrescu, Roman (Tag des Systems Engineering 2025)

Design-for-decarbonization: a framework for decarbonizing cyber-physical production systems at the design stage - Schreiner, Nick; Cowen, Adam; Volling, Thomas; Dumitrescu, Roman (Proceedings of the Design Society)
ABSTRACT: Cyber-physical production systems (CPPS) are responsible for a significant portion of manufacturers’ carbon emissions. Since 80% of product-related environmental impacts are determined at the design stage, there is a need for CPPS manufacturers to focus on decarbonization at the design stage. To date, there is a lack of design-for-decarbonization guidance for CPPS. This paper proposes a procedural framework for the effective selection of decarbonization measures for the design of CPPS. A Decarbonization Wheel is developed to establish a product-specific decarbonization strategy. This tool is linked to a catalogue of decarbonization measures. A measure prioritization logic provides a structure for systematizing selected measures. The framework is validated in the case of an intelligent industrial control valve.

Implementation of a web-based support platform for validation using system architecture in the B2B sector - Humpert, Lynn; Graunke, Jannis; Lewandowski, Lena; Schierbaum, Anja; Dumitrescu, Roman (2025 IEEE International Conference on Recent Advances in Systems Science and Engineering (RASSE))

Product Management: Tasks, Roles, and the Importance of Data - Grigoryan, Khoren; Martin, Lucas; Lamarz, Jessica; Fichtler, Timm; Hohn, Bennett; Asmar, Laban; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)

Industry Perspectives on the Digital Product Passport: A Guide to Sustainable Value Chains From an Engineering Perspective - Trienens, Malte; Schreiner, Nick; Hovemann, Aschot; Dumitrescu, Roman (2025 IEEE European Technology and Engineering Management Summit (E-TEMS))

Product Decarbonization From an Engineering Perspective: Drawing Insights From Industry - Schreiner, Nick; Trienens, Malte; Kürpick, Christian; Asmar, Laban; Dumitrescu, Roman (2025 IEEE European Technology and Engineering Management Summit (E-TEMS))

Seeing the Signs – Supporting School Dog Welfare in England, Germany, the Netherlands and Wales with an Evidence-Based, Teacher-Friendly Dog Ethogram - Mombeck, Mona Maria; Grigg, R.; Lewis, H.; Oostendorp-Godfrey, J.; Pierard, M.; Van der Steen, S.